Soul and mind as quantum states of an embedded human system - Rai D.V.; Kumar G. (My University, 2025)
A human system is a tri-unity with soul, mind and body comprises with various integrated organ system. Soul and mind are the main source of energy that control the physiological and spiritual processes of the human body in which the brain is regarded as microprocessor and worked together with mind. The soul is considered as super-controller and universal consciousness energy state in the body. The present study is designed to understand the quantum states of soul and mind of embedded human system and their relationships. The quantum states and flow of energy are illustrated using band theory and feedback circuit. The role, effect and relationships of yoga, meditation and spirituality were also analyzed. It has been found that soul is an ultimate source of positive energy, modulates the mind and physiological functions of the body and helps to establish a secure communication with the spirituality. The mind with both positive and negative energies, plays an important role for controlling the physiological processes of the body. The yoga, meditation and spirituality provides positive energy to the body, mind and soul and helps to eliminate the negative energy generated by the components of the embedded human body. The study provides deep insight about the relationship, interaction and coordination of soul, mind and body. We hope that the present study will provide a support in understanding the scientific basis of internal energy and informational knowledge to bridge the gap between modern and Vedic sciences in overall integrated multidimensional function of the human system. © 2020 IJSTR.